Características fermentativas e valor nutritivo de silagens de capim-elefante contendo subprodutos do urucum, caju e manga - Telles, Margareth Maria (2006)
This research was carried out at the Forage Research Sector – NPF/DZ/CCA/UFC. The chemical and fermentative characteristics elephant grass silages with increasing levels of annatto by-product processing (ABP) addition at ensiling were evaluated. The following treatments were used: T1 – Elephant grass silage, T2 - Elephant grass silage with 4% of annatto seed by-product processing (ABP), T3 - Elephant grass silage with 8% of ABP, T4 - Elephant grass silage with 12% of ABP and T5 - Elephant grass silage with 16% of ABP, on a fresh matter basis. A randomized completely design with four replicates was adopted. As experimental silos, plastic drums of 210 L were used. The dry matter (DM), the organic matter (OM), the crude protein (CP), the neutral detergent fiber (NDF), the acid detergent fiber (ADF), the hemicelluloses, the ether extract (EE), the total carbohydrates (TC), the non-fibrous carbohydrates (NFC), the neutral detergent insoluble nitrogen (NDIN,% total N), the acid detergent insoluble nitrogen (ADIN, % total N), the pH values, the ammonia nitrogen (in percentage of the total nitrogen, N-NH3, % total N), the lactic acid, the acetic acid, the butyric acid and the propionic acid levels were determined. A linear increasing effect (P<0.01) of the ABP addition on the DM, OM, CP, EE, NFC, acid propionic levels and on the pH values was verified. There was no significant difference among the silages on the hemicellulose, NDIN (% total N), lactic acid,acetic acid and acid butyric levels. With regard to ADIN (% total N) and N-NH3 (% total N) there was a quadratic effect and to NDF, ADF and TC a decreasing linear effect of the ABP addition was observed. One concludes that ABP improves the chemical and fermentative characteristics of the silages, recommending 16% of addition, in a fresh matter basis, at the elephant grass ensilage.